Does corporate governance contribute towards financial information disclosure in Malaysian listed banks? - Htay, Sheila Nu Nu (2012)
Financial information disclosed in the annual report is one of the main sources that investors are interested to make informed judgment in their decision for investment. Due to the financial crisis, Malaysian Code on Corporate Governance was introduced and this Code mentions that one of the tasks of the directors is to provide timely and useful information disclosure. However, in Malaysia, there is not much study on the corporate governance in the banking sector even though this industry is the heart of the country economy. Thus, this study investigates whether corporate governance can contribute to have better financial information disclosure of Malaysian listed bank by using a panel data regression analysis. Corporate governance variables are the board leadership structure, board composition, board size, director ownership, institutional ownership and block ownership. Disclosure index is developed by researcher and conducts content analysis by cross checking between the information disclosure in the annual reports and the disclosure index. The opinion of accountants and financial analysts are used to compute weighted disclosure score because they are preparers and users of the accounting information. This research finds that separate board leadership structure, higher proportion of independent directors on the board, smaller board size, higher director ownership, higher institutional ownership and lower block ownership have higher financial information disclosure.